Seizure-like activity in hyaluronidase-treated dissociated hippocampal cultures - Maria eVedunova; Maria eVedunova; Tatiana eSakharnova; Tatiana eSakharnova; Elena eMitroshina; Elena eMitroshina; Maya ePerminova; Maya ePerminova; Yuri eZakharov; Alexey ePimashkin; Alexander eDityatev; Alexander eDityatev; et al. (Frontiers in Cellular Neuroscience, 2013)
The extracellular matrix (ECM) plays an important role in use-dependent synaptic plasticity. Hyaluronic acid (HA) is the backbone of the neural ECM, which has been shown to modulate -amino-3-hydroxyl-5-methyl-4-isoxazolepropionate (AMPA) receptor mobility, paired-pulse depression, L-type voltage-dependent Ca2+ channel (L-VDCC) activity, long-term potentiation and contextual fear conditioning. To investigate the role of HA in the development of spontaneous neuronal network activity, we used microelectrode array recording and Ca2+ imaging in hippocampal cultures enzymatically treated with hyaluronidase. Our findings revealed an appearance of epileptiform activity 9 days after hyaluronidase treatment. The treatment transformed the normal network firing bursts and Ca2+ oscillations into long-lasting superbursts and superoscillations with durations of 11-100 seconds. The changes in Ca2+ transients in hyaluronidase-treated neurons were more prominent then in astrocytes and preceded changes in electrical activity. The Ca2+ superoscillations could be suppressed by applying the L-VDCC blocker diltiazem, whereas the neuronal firing superbursts could be additionally suppressed by an 6-cyano-7-nitroquinoxaline-2,3-dione as an antagonist of AMPA/kainate receptors. These results suggest that changes in the expression of HA can be epileptogenic and that hyaluronidase treatment in vitro provides a robust model for the dissection of the underlying mechanisms.